Successful Treatment of Myasthenia Gravis Following PD-1/CTLA-4 Combination Checkpoint Blockade in a Patient With Metastatic Melanoma - Werner, Jan-Michael; Schweinsberg, Viola; Schroeter, Michael; von Reutern, Boris; Malter, Michael P.; Schlaak, Max; Fink, Gereon R.; Mauch, Cornelia; Galldiks, Norbert (Frontiers in Oncology, 2019)
Currently, the blockade of certain immune checkpoints such as the cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed cell death-1 (PD-1) using checkpoint inhibitors is standard of care in patients with metastatic melanoma, especially with BRAF wild-type. However, several checkpoint inhibitor-related complications have been reported, including severe adverse events in the central and peripheral nervous system. In particular, in the recent past, the occurrence of myasthenia gravis following checkpoint inhibitor monotherapy, particularly nivolumab or ipilimumab, has been reported. In contrast, reports on PD-1/CTLA-4 double blockade - usually with fatal clinical outcome - are scarce. We here report a case with double immune checkpoint blockade-related myasthenia gravis with favorable clinical outcome.